Use of probiotics in vaginal infections - Castro, Francisca Loaiza; Chancay, Ricardo Carvajal; Toledo, Anthony Rojas; Tello, Nataly Ontaneda; Zavala, Jeordy Becerra; Melo, Cristina Pacheco; Moyano, Emily Dennise (International Journal of Research in Medical Sciences, 2025)
Vaginal infections are characterized by an overgrowth of microorganisms opportunistic and decreased levels of Lactobacillus. Vaginosis is common in women of childbearing age, perimenopausal women, women with polycystic ovary syndrome, pregnant women and adolescents. Vaginosis is often underestimated or misdiagnosed. Multiple studies mention that vaginosis detection tests should be performed on all high-risk pregnancies, women with significant obstetric history such as premature abortions and those who suffer from tuberculosis, because they are a risk factor for the development of abortions, premature rupture of membranes, choriomanionitis or preterm births. A challenge that is becoming more and more common revolves around the resistance of the microorganisms that cause vaginosis to the established treatments, generating recurrent and multi-resistant infections. For the treatment of different vaginosis, antibiotics and antifungals are prescribed. Studies point out the importance of prescribing antibiotics together with probiotics and thus avoiding dysbiosis in order to avoid recurrence of vaginal infections. Probiotics must be administered in the necessary dose and time so that they can generate a positive effect. More than 80% of Lactobacillus species must be present in a probiotic to ensure adequate acid and bactericidal production to prevent microfilm formation. The results of the use of probiotics will depend on the quality of the formula and the maintenance of the cold chain.